Peningkatan Hasil Belajar Mahasiswa melalui Forum Diskusi Online di Jurusan PGSD FKIP Universitas Syiah Kuala - Mislinawati Mislinawati; Linda Vitoria; Intan Safiah; Said Darnius (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2022)
The use of online discussion is an alternative mode of learning during the pandemic. The purpose of this study was to determine the effect of online discussion forums on the learning outcomes of the students at PGSD FKIP Universitas Syiah Kuala, especially in the Lesson Planning course. This study used a pre-experimental research method with a One-Group Pretest-Posttest Design. The research was conducted in the Even Semester of the 2020/2021 Academic Year. 17 students participated in the study. Through hypothesis testing using a paired sample t-test with a significance level of 5%, it was found that there was a significant difference between students’ learning outcome before and after the use of online discussion. Thus, it can be concluded that there is a significant effect of the use of online discussion forums on students’ learning outcomes at PGSD FKIP Universitas Syiah Kuala.